Complementary and Integrative Medicines Used by Cancer Patients to Cope With Chemotherapy-Related Taste Alterations - Yasemin Yildirim; Tugbamenekli Tugbamenekli (Journal of Holistic Nursing and Midwifery)
Introduction: Cancer is a global health problem. Taste change is one of the most common symptoms in cancer patients undergoing chemotherapy. Cancer patients often use Complementary and Integrative Medicine (CIM) to manage chemotherapy complications. Objective: This study aimed to evaluate CIM used by cancer patients to cope with chemotherapy-related taste alterations. Materials and Methods: This cross-sectional study was carried out on 318 cancer patients receiving chemotherapy in an oncology hospital in Malatya City, Turkey. The samples were recruited by convenience sampling method. The study data were collected with a data form developed by the research team. Written permissions were obtained from all participants and the Ethics Committee. Frequencies, mean scores, and standard deviation were used to present descriptive findings. The independent t-test, Chi-square test, and multivariate logistic regression analysis were used to analyze the obtained data. Results: The Mean±SD age of the patients was 65.18±8.36 years, and the mean duration of their diseases was 35.34±16.27 months. About 54.1% of the patients were female, and 42.8% had some information about CIM. Their primary source of information was other patients (49.6%), and 34.9% used CIM to cope with chemotherapy-related taste alterations. The most common method used was phytotherapy (50.5%), and the most commonly used herb was miracle fruit (21.4%). It was also determined that the frequency of CIM use was affected by age, illness duration, gender, living in a city, family history of cancer, having breast cancer, having information on CIM, having metastasis, and lacking complications (R2= 0.426, P=0.025). Conclusion: Cancer patients frequently use CIM to cope with chemotherapy-related taste alterations, and phytotherapy was the most commonly-used CIM.